PERBEDAAN SENAM OTAK DAN SENAM POCO-POCO MENINGKATKAN FUNGSI EKSEKUTIF LANSIA: STUDI EKSPERIMENTAL DI PUSAT SANTUNAN KELUARGA - Yuliana Yosephine; Rr Josephine Retno Widayanti; Yuda Turana (PERDOSNI, 2020)
THE DIFFERENCE OF BRAIN GYM AND POCO-POCO GYMNASTICS IMPROVING EXECUTIVE FUNCTION OF ELDERLY: EXPERIMENTAL STUDY IN PUSAT SANTUNAN KELUARGAABSTRACTIntroduction: The elderly have the risk of experiencing executive dysfunction due to structural and functional changes in neurons and synapses in the prefrontal cortex associated with aging. The brain gym and Poco-poco gymnastics can maintain and improve executive function so that productivity and quality of life of theelderlyremainoptimal.Aim: To find out the difference between the effect of brain gym and Poco-poco gymnastics on improving the executive function of elderly population in Pusat Santunan Keluarga (PUSAKA).Method: The study uses an experimental study with a nonequivalent control group design approach. Sixty elderly respondents were dividedinto the brain gym group (n=30) and the Poco-poco gymnastics group (n=30) in two different PUSAKAs. Each interventions are carried out three times a week for 30 minutes in four weeks. Analysis of the differences in the effect of brain gym and Poco-poco gymnastics on executive function of the elderly based on the mean difference in Oral Trail Making Test Form B (OTMT-B) using the Mann-Whitney test.Result: There was an improvement in the mean duration of completion of OTMT-B after the intervention in the brain gym group and Poco-poco gymnastics group with a significant p<0.05. The difference in mean difference between OTMT-B after the intervention in the Poco-poco gymnastics group was higher than the brain gym group.Discussion: The brain gym and Poco-poco gymnastics can improve the function of the elderly executive function. Improved executive function was more significant in the Poco-poco gymnastics group than the brain gym group.Keyword: Brain gym, elderly, executive function, Oral Trail Making Test Form-B, Poco-poco gymnasticsABSTRAKPendahuluan: Lansia berisiko mengalami gangguan fungsi eksekutif karena perubahan struktural dan fungsional pada neuron dan sinaps di korteks prefrontalis terkait penuaan. Senam otak dan senam Poco-poco dapat mempertahankan dan meningkatkan fungsi eksekutif sehingga produktivitas dan kualitas hidup lansia tetap optimal.Tujuan: Untuk mengetahui perbedaan pengaruh senam otak dan senam Poco-poco terhadap peningkatan fungsi eksekutif populasi lansia di Pusat Santunan Keluarga (PUSAKA).Metode: Penelitian menggunakan studi eksperimental dengan pendekatan nonequivalent control group design. Enam puluh lansia sebagai subyek terbagi dalam kelompok senam otak (n=30) dan kelompok senam Poco-poco (n=30) di dua PUSAKA. Masing-masing intervensi dilakukan sebanyak tiga kali seminggu selama 30 menit dalam empat minggu. Analisis perbedaan pengaruh senam otak dan senam Poco-poco terhadap fungsi eksekutif lansia berdasarkan selisih rerata Oral Trail Making Test Form B (OTMT-B) menggunakan uji Mann-Whitney.Hasil: Terdapat perbaikan durasi penyelesaian OTMT-B setelah intervensi senam otak dan senam Poco-poco dengan nilai kemaknaan p<0,05. Perbedaan selisih rerata durasi penyelesaian OTMT-B pada kelompok intervensi senam Poco-poco lebih tinggi dibandingkan kelompok senam otak.Diskusi: Intervensi senam otak dan senam Poco-poco dapat meningkatkan fungsi eksekutif populasi lansia. Peningkatan fungsi eksekutif lebih signifikan pada kelompok intervensi senam Poco-poco dibandingkan kelompok intervensi senam otak.Kata kunci: Fungsi eksekutif, lanjut usia, Oral Trail Making Test Form-B, senam otak, senam Poco-poco